Comparative efficacy of different modalities of transcranial magnetic stimulation for treating Parkinson’s disease with depression: a systematic review and network meta-analysis - Wang, Zhichen; Chen, Senlin; Zhu, Qianhong; Chen, Shun; Zou, Yulong; Chen, Gengzhao; Luo, Qiuyi; Huang, Sai’e (Frontiers in Neurology, 2025)
ObjectiveParkinson’s disease (PD) is a prevalent neurodegenerative disorder. However, systematic comparisons of various transcranial magnetic stimulation (TMS) modalities for treating depression in patients with PD remain limited. This study aimed to evaluate the therapeutic effects of different TMS modalities on depression in patients with PD.MethodsA systematic search following PRISMA guidelines was conducted in the following databases: Cochrane Library, Embase, PubMed, Web of Science, CNKI, WanFang, VIP, and CBM, covering literature up to April 1, 2025. Included studies were randomized controlled trials (RCTs) evaluating TMS interventions in PD patients with depression. Risk of bias was assessed using the Cochrane Risk of Bias 2.0 (ROB 2.0) tool. Comparative effectiveness analysis was conducted using STATA 17.0.ResultsA total of thirty-five RCTs involving 2,353 participants were included, evaluating high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) and low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) compared to sham stimulation and conventional rehabilitation therapy (CRT). The results showed that LF-rTMS [standardized mean difference (SMD) = −2.46, 95% confidence interval (−3.62, −1.29)], HF-rTMS [SMD = −2.05, 95% CI (−3.16, −0.94)] significantly improved depressive symptoms.ConclusionThe network meta-analysis indicates that both HF-rTMS and LF-rTMS may be considered as effective adjunctive therapy to improve depression in patients with PD, with LF-rTMS potentially showing superior efficacy in improving depressive symptoms. Parameters, such as total pulses no more than 1,200, may optimize outcomes. However, further high-quality RCTs are required to validate these findings and refine optimal treatment protocols.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024564867.